Pengaruh Toxic Friendship terhadap Akhlak Peserta Didik - Januarto, Annas; Damopolii, Muljono; Rusmin B., Muhammad (Faculty of Tarbiyah and Teacher Training, 2025)
Adolescence is a crucial phase in students' social and moral development, where friendships significantly shape their personality and morals. In the educational context, toxic friendships or unhealthy friendships are a concern because they can influence students' behavior and moral values at school. This study aims to analyze the influence of toxic friendships on students' morals at SMP Negeri 1 Kendari. The method used was quantitative with an ex post facto approach. The study sample consisted of 69 students selected from a population of 343 students using a proportionate random sampling technique. Data were collected through questionnaires and analyzed using simple linear regression analysis. The results showed that toxic friendships significantly influenced students' morals. This finding suggests that unhealthy friendships negatively impact moral formation, although other factors also play a role. The implications of this study emphasize the importance of the school's role in providing insight and recommendations regarding the influence of toxic friendships on students' morals.